ARTIFICIAL INTELLIGENCE FOR SUSTAINABLE ARCHITECTURE: SMART GREEN BUILDINGS IN UZBEKISTAN (Uzbekistan Open Conference, 2025)
Uzbekistan, a leading Central Asian country in terms of digital transformation and AI adoption, is embracing intelligent technologies to enhance the sustainability of its built environment. This study explores the application of artificial intelligence in the design and energy optimization of green buildings across urban centers such as Tashkent, Samarkand, and Bukhara. By leveraging machine learning, computer vision, and IoT-integrated data streams, this research demonstrates how AI contributes to reducing energy consumption, optimizing HVAC performance, and supporting real-time energy monitoring. Through a case study methodology combined with predictive modeling and empirical evaluation, the study illustrates a comprehensive AI-driven framework for smart sustainable buildings tailored to Uzbekistan’s climate, urban density, and energy infrastructure.